HUBUNGAN KINERJA KADER KESEHATAN DENGAN KEPUASAN IBU BAYI DAN BALITA DI DESA PURWODADI WILAYAH KERJA PUSKESMAS PADANG PANYANG KABUPATEN NAGAN RAYA - Anasril, Anasril; Bustami, Bustami; Maryono, Maryono (SINERGI : Jurnal Riset Ilmiah, 2025)
The success of Posyandu is largely determined by the performance of cadres who are also cadres of Family Empowerment and Welfare (PKK) as well as guidance provided by the PKK mobilizing team, especially the District / City PKK mobilizing team. Problems in the implementation of Posyandu are caused, among others, by the lack of cadres, many drop-outs of cadres, passivity of Posyandu administrators because there has been no formation or resuffle of new administrators of these activities. This thesis aims to determine the relationship between the performance of health cadres and the satisfaction of mothers of infants and toddlers in Gampong Purwodadi, Kuala Pesisir District, Nagan Raya Regency in 2024. The research design used was Crossectional Study, with a sample size of 43 people. Data analysis using the chi-square test with a significance value (α = 0.05). The results showed that most mothers of infants and toddlers in Gampong Purwodadi, Padang Panyang Health Center working area, Nagan Raya Regency stated that the performance of cadres was in the good category, namely 60.5%, the level of maternal satisfaction was mostly in the satisfied category, namely 50.5%.  The results of the analysis showed that there was a relationship between the performance of cadres and the satisfaction of mothers of infants and toddlers with a p-value = 0.010. It is recommended to Health Officers at the Padang Panyang Health Center, Nagan Raya Regency to further increase support and motivation to health cadres so that services are even better.